Frequent neurologic manifestations and encephalopathy‐associated morbidity in Covid‐19 patients. Issue 11 (5th October 2020) - Liotta, Eric M.; Batra, Ayush; Clark, Jeffrey R.; Shlobin, Nathan A.; Hoffman, Steven C.; Orban, Zachary S.; Koralnik, Igor J.
Abstract: Objective: Covid‐19 can involve multiple organs including the nervous system. We sought to characterize the neurologic manifestations, their risk factors, and associated outcomes in hospitalized patients with Covid‐19. Methods: We examined neurologic manifestations in 509 consecutive patients admitted with confirmed Covid‐19 within a hospital network in Chicago, Illinois. We compared the severity of Covid‐19 and outcomes in patients with and without neurologic manifestations. We also identified independent predictors of any neurologic manifestations, encephalopathy, and functional outcome using binary logistic regression. Results: Neurologic manifestations were present at Covid‐19 onset in 215 (42.2%), at hospitalization in 319 (62.7%), and at any time during the disease course in 419 patients (82.3%). The most frequent neurologic manifestations were myalgias (44.8%), headaches (37.7%), encephalopathy (31.8%), dizziness (29.7%), dysgeusia (15.9%), and anosmia (11.4%). Strokes, movement disorders, motor and sensory deficits, ataxia, and seizures were uncommon (0.2 to 1.4% of patients each). Severe respiratory disease requiring mechanical ventilation occurred in 134 patients (26.3%). Independent risk factors for developing any neurologic manifestation were severe Covid‐19 (OR 4.02; 95% CI 2.04–8.89; P < 0.001) and younger age (OR 0.982; 95% CI 0.968–0.996; P = 0.014). Of all patients, 362 (71.1%) had a favorable functional outcome at discharge (modified Rankin Scale 0–2). However, encephalopathy was independently associated with worse functional outcome (OR 0.22; 95% CI 0.11–0.42; P < 0.001) and higher mortality within 30 days of hospitalization (35 [21.7%] vs. 11 [3.2%] patients; P < 0.001). Interpretation: Neurologic manifestations occur in most hospitalized Covid‐19 patients. Encephalopathy was associated with increased morbidity and mortality, independent of respiratory disease severity.